Electropulse-produced bio-inspired steel with soft-hard phases to solve conflicting demands of hardness and impact toughness - Chao Wu; Yang Zhao; Xiaofeng Xu; Yachong Zhou; Xudong Yan; Zhicheng Wu; Lai We; Xiaoming Qiu (Journal of Materials Research and Technology, 2023)
To solve two conflicting demands of hardness and impact toughness, we learn from nature and provide a novel strategy to fabricate bio-inspired steel based on electropulsing, which produces self-generated hard blocks on the soft matrix without composition change. The results show that current parameters can well control the size and hardness of hard blocks, and thus the appropriate combination of soft and hard blocks can be selected to meet the actual working requirements. The bio-inspired steel exhibits excellent comprehensive performance. The wear resistance, elongation, and impact toughness of the bio-inspired steel are about 7.99 × 106 N m/g, 22.6% and 196.3 J/cm2, respectively, which are 22%, 232%, and 542% higher than that in the traditional quenched samples. Moreover, the hard blocks protrude, and specimens show a non-smooth surface after deformation. For the specimen with elongation of 20%, its wear resistance further increases to 9.16 × 106 N m/g, which is about 14.6% higher than the specimens without morphological change and about 39.8% higher than the traditional quenched specimens.